Analysis of variable fluid properties for three-dimensional flow of ternary hybrid nanofluid on a stretching sheet with MHD effects - Yasmin Humaira; Ullah Jan Saeed; Khan Umar; Islam Saeed; Ullah Aman; Muhammad Taseer (Nanotechnology Reviews)
This study presents a novel model for variable fluid properties of a ternary hybrid nanofluid with base fluid polymer suspended on a three-dimensional stretching sheet under the influence of magnetohydrodynamic forces. Viscosity and thermal conductivity are temperature-dependent. This model has potential for use in nanotechnology, particularly in the shaping and design of surfaces for devices that can stretch or contract, wrap, and paint. The nonlinear equations in charge of this physical problem are derived by using similarity transformations. The fluid behavior is examined using the Reynolds viscosity model. The coupled nonlinear governing equations and the necessary boundary conditions are solved using the shooting technique with RK-4. The numerical calculations, including velocity and temperature profiles, are presented graphically to give the results a physical interpretation. The table discusses skin friction and Nusselt numbers at various physical parameters. The study’s findings show that changing the stretching parameter causes a significant change in the flow characteristics. Particularly, the thickness of the boundary layer decreases as the volume fraction of nanoparticles rises. Furthermore, because temperature-dependent viscosity is taken into account, as the viscosity parameter increases, so does the temperature. Key results specify that the Nusselt number Nu{\rm{Nu}} increases with the increase in temperature-dependent viscosity αα , while decreases with the increase in thermal conductivity ϵε parameters. Impact of αα shows more convective heat transfer. Greater values of ϵε reduce the effectiveness of heat transfer.